The ideological origins of the condemnation that Herculano and Oliveira Martins made of the discoveries and conquests - Ramos, Rui (1997)
This article concerns the negative assessments of the fifteenth and sixteenth century discoveries and conquests that are found in contemporary Portuguese historiography. The focus is on the work of Alexandre Herculano and J. P. Oliveira Martins, the most important Portuguese historians of the nineteenth century. Herculano and Oliveira Martins reacted to the discoveries and conquests in a way that is explained by the influence of the republican tradition. Republicanism favoured a model of political community based on a stable relationship between a population of independent producers and a geographical area. For example, it was this model that inspired Mouzinho da Silveira's legislation in 1932. In the works of Herculano and Oliveira Martins, denigration of the overseas expansion was a result of their fascination with this republican model.